2020
DOI: 10.1109/access.2020.2995040
|View full text |Cite
|
Sign up to set email alerts
|

Performance Analysis of Routing Protocols for UAV Communication Networks

Abstract: The design of routing protocol is an important and key problem in unmanned aerial vehicle (UAV) communication networks. In low altitude environment, UAV information transmission is a complex task. It is an important scientific challenge to design a routing protocol that can provide efficient and reliable node to node packet transmission. This paper develops a more realistic simulation environment based on OPNET 14.5, and performs performance tests and comparisons on four classic routing protocols: Ad Hoc on de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…In UAV group networks [260,261], the mobility and altitude of UAVs, transmitted power, inter-UAV distances, extraneous noise, uneven UAV access users' traffic distribution in both spatial and temporal domains, will largely affect the routing protocol [262] and conventional routing protocols fail to work. Several novel routing algorithms have been proposed recently for UAV group networks to achieve better performance [263][264][265][266][267][268]. Nevertheless, routing strategies which can adapt to high mobility, dynamic topology, and different routing capabilities in LEO satellite networks and UAV group networks are still in their early stage and need further studies.…”
Section: Space-air-ground-sea Integrated Networkmentioning
confidence: 99%
“…In UAV group networks [260,261], the mobility and altitude of UAVs, transmitted power, inter-UAV distances, extraneous noise, uneven UAV access users' traffic distribution in both spatial and temporal domains, will largely affect the routing protocol [262] and conventional routing protocols fail to work. Several novel routing algorithms have been proposed recently for UAV group networks to achieve better performance [263][264][265][266][267][268]. Nevertheless, routing strategies which can adapt to high mobility, dynamic topology, and different routing capabilities in LEO satellite networks and UAV group networks are still in their early stage and need further studies.…”
Section: Space-air-ground-sea Integrated Networkmentioning
confidence: 99%
“…Traditional routing protocols have developed rapidly in the last few decades. The authors of [23] carried out performance tests and comparisons concerning classical routing protocols for AODV, OLSR, Dynamic Source Routing (DSR), and the geographic routing protocol (GRP). The simulation results indicate that different routing protocols can be used in different UAV communication network scenarios.…”
Section: Conventional Routing Protocolmentioning
confidence: 99%
“…This self‐organized model is developed to maintain the speed and mobility during the transmission to optimize the residual energy of the node. Zafar et al 14 suggested a multiple cluster based topology where a separate link table is maintained among the neighbor nodes to analyze the performance parameters of the other node to optimize the energy consumption. Bhandari et al 15 suggested a dynamic clustering framework where the overheads are reduced by limiting the resources to stabilize the network.…”
Section: Related Workmentioning
confidence: 99%